Pharmacological interventions for the prevention of bleeding in people undergoing elective hip or knee surgery: a systematic review and network meta‐analysis - Gibbs, VN; Champaneria, R; Sandercock, J; Welton, NJ; Geneen, LJ; Brunskill, SJ; Dorée, C; Kimber, C; Palmer, AJR; Estcourt, LJ (Cochrane Collaboration, 2024)
Background Hip and knee replacement surgery is a well‐established means of improving quality of life, but is associated with a significant risk of bleeding. One‐third of people are estimated to be anaemic before hip or knee replacement surgery; coupled with the blood lost during surgery, up to 90% of individuals are anaemic postoperatively. As a result, people undergoing orthopaedic surgery receive 3.9% of all packed red blood cell transfusions in the UK. Bleeding and the need for allogeneic blood transfusions has been shown to increase the risk of surgical site infection and mortality, and is associated with an increased duration of hospital stay and costs associated with surgery. Reducing blood loss during surgery may reduce the risk of allogeneic blood transfusion, reduce costs and improve outcomes following surgery. Several pharmacological interventions are available and currently employed as part of routine clinical care.